A framework of tqm and organizational performance with ISO 9001 and innovation as mediators in Iraqi Manufacturing Companies - Abdulsalam, Najdat Hameed (2022)
Total Quality Management (TQM) has become a crucial strategy for companies to maintain their position in the advent of globalization and market competition. At the same time, ISO9001 and innovation have been widely used by companies to gain continuous competitiveness and financial benefits. Unfortunately, limited studies have focused on the relationships between TQM, ISO9001, innovation and organizational performance (OP) in Iraqi manufacturing companies. This study aims to develop a new TQM framework towards improving organizational performance with mediating effects of ISO9001 and innovation in Iraqi manufacturing companies. To achieve this aim, the research approach adopted a quantitative method. A survey was used as the research method, and data was collected using a questionnaire. The respondents involved directors, managers, engineers and executives. One hundred eighty-three usable questionnaires were returned, yielding a 53.83% percent response rate. The findings of the survey were analysed using Partial Least Square (PLS) based on Structural Equation Modelling (SEM) software. The hypotheses were tested to establish the relationships between TQM Practices and OP as well as determine the mediating effects of innovation and ISO9001. The result indicated a significant relationship between TQM and OP (β= 0.468, p<0.01), TQM and ISO 9001 (β = 0.710, p<0.01), TQM and innovation (β =0.516, p<0.01), ISO9001 and innovation (β = 0.267, p<0.01) as well as innovation and OP (β = 0.336, p<0.01). While, there is no significant relationship between ISO 9001 and OP (β = -0.112, p>0.01). It is found that innovation gives a positive relationship between TQM practices and OP as a mediator, whilst the ISO9001 implementation was not supporting to the relationship between TQM practices and OP. The results of this study are beneficial and act as a guide for Iraqi manufacturing managers and practitioners to improve their organizational performance.